Atomic Layer Deposition of Nickel Nitride Thin Films using NiCl2(TMPDA) and Tert‐Butylhydrazine as Precursors. Issue 11 (1st April 2019) - Väyrynen, Katja; Hatanpää, Timo; Mattinen, Miika; Heikkilä, Mikko J.; Mizohata, Kenichiro; Räisänen, Jyrki; Link, Joosep; Stern, Raivo; Ritala, Mikko; Leskelä, Markku
Abstract : This article describes the atomic layer deposition (ALD) of nickel nitride and nickel thin films using a diamine adduct of Ni(II) chloride, NiCl2 (TMPDA) (TMPDA = N, N, N′, N′, ‐tetramethyl‐1, 3‐propanediamine), as the metal precursor. Owing to the high reducing power of tert‐butylhydrazine (TBH), the films are grown at low temperatures of 190–250 °C. This is one of the few low‐temperature ALD processes that can be used to grow Ni3 N and Ni metal on both insulating and conductive substrates. The films are characterized in terms of crystallinity, morphology, composition, resistivity, and coercivity. X‐ray diffraction shows reflections compatible with either hexagonal Ni or Ni3 N. Composition analyses suggest that the films are close to stoichiometric Ni3 N. Despite the nitride component, the films exhibit low resistivity values and at the lowest, a resistivity of 37 μΩ cm is achieved. The result is lower than what is typically observed for Nix N films and not much higher than the best results concerning ALD Ni metal. The nitrogen content of the films is lowered down to 1.2 at% by postdeposition reduction at 150 °C in 10% forming gas. After the reduction, the nonmagnetic nitride films are converted to ferromagnetic Ni metal. Abstract : A new precursor combination is found for depositing high‐quality Ni3 N thin films by atomic layer deposition (ALD). The films are grown using a new, low‐cost Ni precursor and tert‐butylhydrazine as the reducing agent. The film growth proceeded through saturative, self‐limiting surface reactions and afforded films with low resistivity. Ferromagnetic Ni metal films are obtained by postdeposition reduction.